RNA‐based biocontrol compounds: current status and perspectives to reach the market. Issue 3 (17th December 2019) - Taning, Clauvis NT; Arpaia, Salvatore; Christiaens, Olivier; Dietz‐Pfeilstetter, Antje; Jones, Huw; Mezzetti, Bruno; Sabbadini, Silvia; Sorteberg, Hilde‐Gunn; Sweet, Jeremy; Ventura, Vera; Smagghe, Guy
Abstract: Facing current climate challenges and drastically reduced chemical options for plant protection, the exploitation of RNA interference (RNAi) as an agricultural biotechnology tool has unveiled possible new solutions to the global problems of agricultural losses caused by pests and other biotic and abiotic stresses. While the use of RNAi as a tool in agriculture is still limited to a few transgenic crops, and only adopted in restricted parts of the world, scientists and industry are already seeking innovations in leveraging and exploiting the potential of RNAi in the form of RNA‐based biocontrol compounds for external applications. Here, we highlight the expanding research and development pipeline, commercial landscape and regulatory environment surrounding the pursuit of RNA‐based biocontrol compounds with improved environmental profiles. The commitments of well‐established agrochemical companies to invest in research endeavours and the role of start‐up companies are crucial for the successful development of practical applications for these compounds. Additionally, the availability of standardized guidelines to tackle regulatory ambiguities surrounding RNA‐based biocontrol compounds will help to facilitate the entire commercialization process. Finally, communication to create awareness and public acceptance will be key to the deployment of these compounds. © 2019 Society of Chemical Industry Abstract : This study highlights the expanding research and development pipeline, commercial landscape, regulatory environment and the importance of good communication surrounding the pursuit of RNA‐based biocontrol compounds with improved environmental profiles.